Beginning Elastic Stack - Sharma, Vishal (Apress : Imprint: Apress, 2016)
This book teaches you how to install, configure and implement the Elastic Stack (Elasticsearch, Logstash and Kibana) - the invaluable tool for anyone deploying a centralized log management solution for servers and apps. Supported by Puppet and available with various plugins, Elastic Stack is the best option for your server log management. You will learn how to use and configure Elastic Stack independently and alongside Puppet. Each chapter includes real-world examples and practical troubleshooting tips, enabling you to get up and running with Elastic Stack in record time. Fully customizable and easy to use, Elastic Stack enables you to be on top of your servers all the time, and resolve problems for your clients as fast as possible. Get started with it using this book today.